Television and the Modernization Ideal in 1980s China : Dazzling the Eyes. - Wen, Huike (Lexington Books, 2013)
Using theories of visual culture, media technology, globalization and gender studies supplemented by visual images and interviews, the book explores Chinese television history in the pivotal decade of the 1980s from the cultural studies viewpoint and explains the intellectual reception of television in China during the '80s.